2017
DOI: 10.1038/s41598-017-10717-z
|View full text |Cite
|
Sign up to set email alerts
|

PIK3CA exon9 mutations associate with reduced survival, and are highly concordant between matching primary tumors and metastases in endometrial cancer

Abstract: Mutations of the phosphoinositide-3-kinase (PI3K) catalytic subunit alpha gene (PIK3CA) are frequent in endometrial cancer. We sequenced exon9 and exon20 of PIK3CA in 280 primary endometrial cancers to assess the relationship with clinicopathologic variables, patient survival and associations with PIK3CA mRNA and phospho-AKT1 by gene expression and protein data, respectively. While PIK3CA mutations generally had no impact on survival, and were not associated with clinicopathological variables, patients with ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 60 publications
(104 reference statements)
1
35
1
Order By: Relevance
“…As for survival, no signi cant association has been reported between PIK3CA mutations and disease-free survival in 94 EC patients [10]. On the other hand, associations have been reported between PIK3CA missense mutation and unfavorable outcome in grade 3 EEC tumors, and between PIK3CA exon 9 mutations and reduced survival in EC patients [23,24]. In the current study, there were no signi cant associations between the PIK3CA mutation and any clinicopathological features or survival.…”
Section: Discussioncontrasting
confidence: 66%
“…As for survival, no signi cant association has been reported between PIK3CA mutations and disease-free survival in 94 EC patients [10]. On the other hand, associations have been reported between PIK3CA missense mutation and unfavorable outcome in grade 3 EEC tumors, and between PIK3CA exon 9 mutations and reduced survival in EC patients [23,24]. In the current study, there were no signi cant associations between the PIK3CA mutation and any clinicopathological features or survival.…”
Section: Discussioncontrasting
confidence: 66%
“…The protein product of the PIK3CA gene is the catalytic subunit, p110a, in class IA of PI3K 24 . Mutations of PIK3CA have been found in multiple malignant tumors, such as breast cancer 25 , endometrial cancer 26 and bladder cancer 27 . Previous studies have reported that the frequency of PIK3CA mutation in CRC is 7%-32% 8 , 28 31 .…”
Section: Discussionmentioning
confidence: 99%
“…Although there are multiple variations of PIK3CA mutation, the "hot-spot" mutations are located within the helical (exon 9) or kinase (exon [42]. While previous studies have investigated the potential associations between various PIK3CA mutations and clinical prognosis [43][44][45], prediction of pharmacological vulnerability based on these mutations remains elusive. Interestingly, when we evaluated drug sensitivities to PI3K compounds in PIK3CA-mutant tumors, we found that SNVs that lead to E542K amino acid substitution induced the most robust susceptibility to an AKT inhibitor (AZD5363) compared to other PIK3CA mutations (Fig.…”
Section: Pharmacogenomic Landscape Of Gastric Cancermentioning
confidence: 99%